(untitled) (Proceedings of the International Conference on Future of Education, 2021)
: The article aims to discuss the main features of teaching reading in the lessons of RFL (Russian as a foreign language) in the Chinese audience. Foreign language reading is significant speech activity because it is the basis of developing other speech activities. The article analyses the phonetical and methodological barriers, which may meet Chinese students while improving their reading skills, and provide some methods of removing the difficulties in reading. When teaching Russian to Chinese students, especially outside the linguistic environment, teachers do not pay due attention to practicing various types of reading, and, consequently, automating verbal forecasting. In the methodological literature, to overcome oral speech problems, the need to focus on spontaneous oral speech is noted, directly related to reading as a resource for expanding vocabulary and grammatical structures. Using system analysis, comparison, typology, theoretical and methodological forecasting, the work compares the most popular types of reading in China and Russia when teaching international students, analyzes the advantages and disadvantages of using these types of reading. Based on Chinese students’ most frequent difficulties, a developed balanced type text is proposed that considers the most problematic phonetic cases. Also, a system of various exercises is proposed, aimed at developing the skills of oral speech. The exercises and use of phonetically balanced texts might contribute to the further enrichment of RFL methodology.